Comparative effectiveness of traditional Chinese medicine and angiotensin converting enzyme inhibitors, angiotensin receptor blockers, and sodium glucose cotransporter inhibitors in patients with diabetic kidney disease: A systematic review and network meta-analysis. (March 2022) - Zhang, Lili; Miao, Runyu; Yu, Tongyue; Wei, Ruonan; Tian, Feng; Huang, Yishan; Tong, Xiaolin; Zhao, Linhua
Abstract: Angiotensin converting enzyme inhibitors (ACEI), angiotensin receptor blockers (ARB), and sodium glucose cotransporter inhibitors (SGLT2i) are commonly used to treat diabetic kidney disease (DKD). Currently, increasing evidence also suggests traditional Chinese medicine (TCM) as an effective strategy. We assessed the efficacy of ACEI, ARB, SGLT2i, and TCM on major renal outcomes. We searched the electronic literature published up to March 2021 from CNKI, VIP, WanFang, SinoMed, PubMed, Embase, Cochrane Library, Web of Science, and clinicaltrials.gov; a total of 56 studies and 5464 participants were included. We found that TCM plus ACEI, TCM plus ARB, and TCM alone are very effective treatment methods compared with ACEI, ARB, and the placebo in reducing 24-h urine protein, serum creatinine, and blood urea nitrogen. TCM plus ACEI was the most effective treatment (TCM plus ACEI vs. the placebo in 24-h urine protein [mean difference (MD) − 757.18, 95% confidence interval-1177.41 to − 353.31], serum creatinine [MD − 25.81, 95% confidence interval − 35.51 to − 16.03], and blood urea nitrogen [MD − 3.48, 95% confidence interval − 5.04 to − 1.90]). Although the incidence of end-stage renal disease while receiving an TCM plus ARB compared with a placebo was not statistically significant, the treatment ranking showed this combination therapy to have the greatest probability (72.8%) of reducing end-stage renal disease mortality, followed by SGLT2i (68%). Our analyses showed that combining TCM with conventional treatments for patients with DKD can improve renoprotective effects and superiority, and ACEI plus TCM may be the most effective option for treating DKD. Graphical Abstract: ga1